„Za każdą okazyją pisywać listy” – korespondencja jako źródło do badania staropolskich wojaży edukacyjnych - Żołądź-Strzelczyk, Dorota (Biuletyn Historii Wychowania, 2026)
One of the most valuable and richest sources of information about Old Polish education is correspondence. The upbringing of the younger generation has always been considered important from the point of view of the individual, the family, society and the state, hence these issues were given a lot of attention in epistolary sources, both private and official. The plenitude of such sources, their diverse subject matter and the specific nature of this form of communication mean that they can serve as a basis for reconstructing various aspects of Old Polish educational journeys. The archival collections contain many letters written in connection with this type of education. They address issues related to various aspects of living abroad, studying or educational travel. Many people were involved in such trips, writing letters on topics important in the context of the journey. We therefore have letters from trips to domestic schools, journeys to foreign countries, written by travelling young people, their guardians and letters sent from home by parents, and finally letters from strangers who were interested in the affairs of young travellers.